SOSIALISASI DAN INTERNALISASI DALAM PEMBELAJARAN DRUM ANAK-ANAK (Studi Kasus Pengajaran Drum di Lembaga Kursus Musik West Brothers) - Indra Permana (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
ABSTRACT This paper begins with an interest in seeing the musical abilities of children learners of non-formal institutions of West Brothers music course in playing the drum, where the children show "maturity" in the musical. The level of difficulty, the selection of song repertoire, and the stage action presented by the children tends to resemble drum players of adolescence and adulthood. This raises a question about socialization and internalization in learning. West Brothers as an educational institution becomes a place of transmission of knowledge, skills, and values from? educators to learners. In the process of transmission, there is socialization and internalization through social interaction in drum learning activities. This research aims to know how the form of socialization and internalization in the drum learning process in West Brothers, especially in children learners, and how the process of socialization and internalization that form behavior patterns manifest in the musical ability of children playing drum musical instruments. This paper reveals that child behavior patterns embodied in the ability and taste of musical drumming are influenced and shaped through the process of interaction between learners and teachers in the West Brothers environment, including socialization and internalization. Kata kunci : sosialisasi dan internalisasi, west brothers, kursus drum solo